Learning Obstacle the Addition and Subtraction of Fraction in Grade 5 Elementary Schools - Fauzi, Irfan; Suryadi, Didi (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2020)
The Fraction is a material that is very important for students to learn in elementary school, but various difficulties are shown by students in understanding the material, so this study will analyze the learning obstacle that appears to students in the addition and subtraction material in grade 5 elementary school.  The approach in this research uses qualitative and case study methods. The subjects in this study were 5th-grade students of Geger Kalong Girang 1¾2 elementary schools, Bandung City, West Java, Indonesia with a total of 29 students.  Data was collected by tests, interviews, and documentation, while for data analysis techniques using data reduction, data presentation, and conclusions.  The results of this study indicated that students experience learning obstacles, including 1) ontogenic obstacle, which is the inability of students to understand the purpose of the problems presented; 2) epistemological obstacle, namely the inability of students to understand the concept of fractions is part of the whole and the inability of students to do the addition and subtraction of fractions, and; 3) didactical obstacle caused by the presentation of material and the teacher's way of teaching which is only informal.  This research is expected to facilitate students to understand fractions and be a development material in making teaching materials and didactic design of the addition and subtraction fractions based on learning obstacles that appear in this study.